Novel microemulsion containing benzocaine and fusidic acid simultaneously: Formulation, characterization, and in vitro evaluation for wound healing - Arpa, Muhammet Davut; Çağlar, Emre Şefik; Güreşçi, Dilara; Sipahi, Hande; Üstündağ Okur, Neslihan (Springer Science and Business Media Deutschland GmbH, 2024)
Modern drug carrier technologies, such as microemulsions with small droplet sizes and high surface areas, improve the ability of low water solubility active ingredients to permeate and localize. The goal of this study was to create microemulsion formulations for wound healing that contained both fusidic acid (FA), an antibacterial agent, and benzocaine (BNZ), a local anesthetic. Studies on characterization were carried out, including viscosity, droplet size, and zeta potential. The drug-loaded microemulsion had a stable structure with –3.014 ± 1.265 mV of zeta potential and 19.388 ± 0.480 nm of droplet size. In both in vitro release and ex vivo permeability studies, the microemulsion was compared with Fucidin cream and oily BNZ solution. According to the drug release studies, BNZ release from the microemulsion and the BNZ solution showed a similar profile (p > 0.05), while FA release from the microemulsion had a higher drug release compared to Fucidin cream (p < 0.001). The microemulsion presented lower drug permeation (p > 0.05) for both active ingredients, on the other hand, provided higher drug accumulation compared to the control preparations. Moreover, according to the results of in vitro wound healing activity, the microemulsion indicated a dose-dependent wound healing potential with the highest wound healing activity at the highest concentrations. To the best of our knowledge, this developed BNZ- and FA-loaded microemulsion would be a promising candidate to create new opportunities for wound healing thanks to present the active ingredients, which have low water solubility, in a single formulation and achieved higher accumulation than control preparations.
Keywords: Benzocaine; Fusidic Acid; Microemulsion; Wound Healing; L929 Cell Line